Fine structure of the chromospheric activity in Solar-type stars – The Hα line - Lyra, W.; G. F. Porto de Mello (Astronomy and astrophysics (Berlin), 2005)
A calibration of Hα as both a chromospheric diagnostic and an age indicator is presented, complementing the works previously done on this subject ([CITE]; [CITE]). The chromospheric diagnostic was built with a statistically significant sample, covering nine years of observations, and including 175 solar neighborhood stars. Regarding the age indicator, the presence of stars for which very accurate ages are determined, such as those belonging to clusters and kinematic groups, lends confidence to our analysis. We also investigate the possibility that stars of the same age might have gone through different tracks of chromospheric decay, identifying – within the same age range – effects of metallicity and mass. These parameters, however, as well as age, seem to be significant only for dwarf stars, losing their meaning when we analyze stars in the subgiant branch. This result suggests that, in these evolved stars, the emission mechanism cannot be magnetohydrodynamical in nature, in agreement with recent models (Fawzy et al. 2002c, and references therein). The Sun is found to be a typical star in its Hα chromospheric flux, for its age, mass and metallicity. As a byproduct of this work, we developed an automatic method to determine temperatures from the wings of Hα, which means the suppression of the error inherent to the visual procedure used in the literature.